Identifying The Relationship Of Teacher Candidates' Humor Styles With Anxiety And Self-Compassion Levels - AYDIN, AYDAN (ANI YAYINCILIK, 2015)
Problem Statement: Teacher candidates who will soon be responsible for educating the future generations should possess certain characteristics. Specific teacher candidates should have specific characteristics taken into consideration: pre-school and primary teacher candidates should be seen as role models by younger students; psychological counseling and guidance teacher candidates should guide students in terms of choice of profession and provide counseling in case of problems; and special education teacher candidates should be fully equipped with the skills to handle students with special needs and characteristics. Purpose of Study: This study aims to identify the relationship between teacher candidates' humor styles, anxiety, and self-compassion levels, and to investigate these levels from the perspective of gender and grade variables. Method: In this research study, a multiple regression analysis was applied in order to explore the relationship between candidate teachers' humor styles and their anxiety as well as self-compassion levels. The sample of the study is comprised of a total of 1008 students studying in the following departments of the Ataturk Education Faculty at Marmara University: early childhood education, primary school teaching, psychological counseling and guidance, and special education. As data collection instruments, the Self-Compassion Scale, the Humor Styles Questionnaire, and the State and Trait Anxiety Scale were used. Findings and Results: According to the findings of the study, the t values calculated to find the significance of the regression coefficients indicate that isolation and self-judgment sub-dimensions have significant predictiveness for affiliated humor. Self-kindness, common humanity, isolation, and over-identification sub-dimensions have significant predictiveness for self-enhancing humor. Self-kindness, self-judgment, mindfulness, and over-identification subdimensions have significant predictiveness for aggressive humor. Self-judgment and common humanity sub-dimensions have significant predictiveness for self-defeating humor. Other sub-dimensions do not have significant influence on the dependent variable. Finally, the sub-dimensions of the State and Trait Anxiety Scale have significant predictiveness for all the sub-dimensions of the Humor Style Scale. Recommendations: There is a need for experimental studies aiming to boost teacher candidates' self-compassion by developing programs indented to reduce their anxiety levels. It is also suggested that if some aspects of such programs are found to be positive in such studies, they should be incorporated into the optional courses or practice-based applications in the programs of education faculties.
Keywords: Teacher candidates; humor style; self-compassion; anxiety